THE EMPIRICAL BAYES METHOD OF ANALYSIS OF A SERIES OF EXPERIMENTS (Journal of Sciences, Islamic Republic of Iran)
The classical method of analysis of a series of experiments is somewhat involved in being conditional on various, occasionally unrealistic, assumptions such as homogeneity of variances of experimental error, lack of interactions of treatments and places,etc. In this work, we adopt a Bayesian view to account for such heterogeneities. Our appoach is illustrated by a real series of experiments regarding the effect of fertilizers on crops of sugarbeet in various places of Iran. Conjugate priors are considered for parameters of the model and posteriors are obtained. Using iniormation from different places, the unknown priors are estimated and the empirical Bayes procedure is employed